2018
DOI: 10.1016/j.biortech.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherm, kinetic modeling and mechanism of tetracycline on Pinus taeda-derived activated biochar

Abstract: The objective of this study was to evaluate the adsorption of tetracycline (TC) on the Pinus taeda-derived activated biochar (BC). After NaOH activation, the well-developed porous surface structure was observed with a significantly increase in surface area (959.9 m/g). The kinetic and isotherm studies indicated that hydrogen bonding and π-π interaction on the heterogeneous surface would be the possible mechanisms, while intra-particle diffusion was considered as the major limitation for the adsorption of TC on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(146 citation statements)
references
References 33 publications
6
133
0
2
Order By: Relevance
“…Similar conclusions on the effect of pH on tetracycline adsorption were obtained by Jang et al [105], who evaluated a NaOH-activated carbon from Pinus taeda. The study concluded that hydrogen bonding and π-π interaction were the most plausible adsorption mechanisms at low-medium pH values, being intraparticle diffusion a major limitation.…”
Section: Contaminantsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar conclusions on the effect of pH on tetracycline adsorption were obtained by Jang et al [105], who evaluated a NaOH-activated carbon from Pinus taeda. The study concluded that hydrogen bonding and π-π interaction were the most plausible adsorption mechanisms at low-medium pH values, being intraparticle diffusion a major limitation.…”
Section: Contaminantsupporting
confidence: 84%
“…Chemical activation usually begins by the physical mixing step of the activating agent with the biomass precursor [80][81][82]87,88]. Chemical agents include a wide variety of salts, acids or bases, such as H 3 PO 4 [89][90][91], H 2 SO 4 [92,93], ZnCl 2 [94][95][96], FeCl 3 [55,[97][98][99][100][101], NaOH [102][103][104][105] and KOH [102,[106][107][108] among others. In this step, the most relevant variable is the mass ratio between the chemical activating agent and the precursor.…”
Section: Chemical Activationmentioning
confidence: 99%
“…The fitting of the Freundlich model was slightly better than that of the Langmuir model, probably because of high surface heterogeneity of the nanocomposite. 45 Nevertheless, the Langmuir model still simulated the experimental isotherm very well, suggesting the dominance of the monolayer adsorption behavior. 46 The predicted Langmuir maximum adsorption capacity of the 10%-CuO/BC to RR120 reached 1399 mg g −1 , demonstrating the pseudo-first-order k 1 = 6.799 h −1 q e = 53.3 mg g −1 0.767 pseudo-second-order k 2 = 0.202 g mg −1 h −1 q e = 55.9 mg g −1 0.952 Elovich α = 28510.712 mg g −1 h −1 β = 0.182 g mg −1 0.947 Langmuir K L = 0.001 L mg −1 q m = 1399 mg g −1 0.986 Freundlich K f = 4.01 mg (1−n) L n g −1 n f = 0.765 0.992 strong adsorption of the nanocomposite to the anionic dye.…”
Section: Resultsmentioning
confidence: 94%
“…The pseudo-first-order, pseudo-second-order, and Elovich kinetic models as well as the intra-particle diffusion model were used to investigate the kinetics of p-nitrophenol adsorption by biochar 19 . The equations defining these models are reported in the section of the text that follows 20 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Elovich model allowed a better fit of the kinetic data recorded for biochar samples obtained at high pyrolysis temperatures (PC500, PC600, and PC700), as made evident by the relatively high R 2 (0.989-0.995) and low SSE (0.276-0.689) values and more approximate q e . According to the hypothesis at the basis of this model, the energydistribution on the surface of the adsorbent was uneven and chemical adsorption occurred 20,33 .…”
Section: Factors That Impact P-nitrophenol Adsorption Effect Of Adsomentioning
confidence: 99%